2020
DOI: 10.1177/0192512120931209
|View full text |Cite
|
Sign up to set email alerts
|

Tensions between populist and feminist politics: The case of the Spanish left populist party Podemos

Abstract: This paper analyzes the interplay of left populist and feminist politics through a case study of Podemos (‘we can’), a Spanish left populist party that reproduces a dominant gendered logic of politics despite its feminist interpretation of democratic renewal. I argue that this is the result of fundamental contradictions between the feminist and populist projects of political transformation that coexist in the party. Even if left populism offers a more productive terrain for gender equality than right populism,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Feminist scholarship argues that the recent political polarization over gender equality is "part of a broader conflict, where what is truly at stake is the future of democracy" (Graff and Korolczuk 2022, 3). Several studies have analyzed the illiberal core of populist radical right parties' anti-feminist and anti-gender equality stances and concluded that this illiberalism represents a danger to democracy (Alonso and Espinosa-Fajardo 2021;Caravantes 2020;Graff and Korolczuk 2022;Lombardo 2019, 2021).…”
Section: The Study Of Gender Politics Using Parties' Manifestosmentioning
confidence: 99%
See 2 more Smart Citations
“…Feminist scholarship argues that the recent political polarization over gender equality is "part of a broader conflict, where what is truly at stake is the future of democracy" (Graff and Korolczuk 2022, 3). Several studies have analyzed the illiberal core of populist radical right parties' anti-feminist and anti-gender equality stances and concluded that this illiberalism represents a danger to democracy (Alonso and Espinosa-Fajardo 2021;Caravantes 2020;Graff and Korolczuk 2022;Lombardo 2019, 2021).…”
Section: The Study Of Gender Politics Using Parties' Manifestosmentioning
confidence: 99%
“…Traditionally, left-wing parties have represented the interests of the most disadvantaged groups in society, including women. A vast literature on ideology and gender has shown that left-wing parties nominate more women as candidates than right-wing parties (Duverger 1955), have a higher proportion of female parliamentarians (Kittilson 1999;O'Brien 2018), and are more sensitive to women's demands for gender equality (Caravantes 2020;Kantola and Lombardo 2019;Sacchet 2008).…”
Section: Testing the Robustness Of The Rmp Novel Indicators: Three Hy...mentioning
confidence: 99%
See 1 more Smart Citation
“…The other characteristic traits often identified with populism are: persuasive, charismatic style of leadership, assertion of a sense of nostalgia about a glorious, distant (alleged) past, an emotional longing and an 'emotional governance' (Richards, 2013) for bringing forth that past into the future for the native land (Abts and Rummens, 2007;Kampwirth, 2010;Kriesi, 2014). This longing for the homeland and the nostalgia for the 'heartland' are elemental tools of pitting the masses against the 'others' and the elites -the establishments which were neutral (Caravantes, 2021;Elchardus and Spruyt, 2016;Rydgren, 2012;Wodak, 2015).…”
Section: The Hindutva-populismmentioning
confidence: 99%
“…Spain's political system has been polarized since the economic recession of 2008 and the emergence of two competing forms of populism (Vampa, 2020): far-left Podemos (literally "We can") and, more recently, far-right Vox ("Voice" in Latin). Podemos, a party characterized by its many ideological contradictions (Caravantes, 2021), had stood out as the only far-left party to play a key role in Europe (Ramiro and Gómez, 2016), and was the only populist national party in Spain until the electoral success of far-right Vox in 2018 (Turnbull-Dugarte, 2019) and 2019 (Turnbull-Dugarte, Rama and Santana, 2020). The polarization resulting from (or reflected by) the appearance of these two parties in Spain differs from political polarization in the US, where the division between the Democrats and the Republicans remains the driving force of American politics.…”
Section: Introductionmentioning
confidence: 99%